Side-Eye from the Side Kid: Child Sidekicks as Disciplinary Tools in Contemporary Video Games - Emma Joy Reay (Literature)
In this article, I analyse the function of supporting child-characters in contemporary videogames. I integrate Stephen Zimmerly’s typology of sidekicks in Young Adult literature with critical writing on the ‘Daddening’ of videogames, a coinage that refers to the rise in the number of videogames that centre on the filial bond between a father figure and a child. Bringing these ideas into conversation with each other allows me to expand Zimmerly’s sidekick typology to include the ‘Ludic Gateway’, the ‘Morality Certificate’, and the ‘Disciplinary Tool’. I explore each category in greater depth using two case studies: The Last of Us series (2012; 2014; 2020) and the God of War series (2008; 2018; 2022). These commercially successful, critically acclaimed franchises rely on young deuteragonists to humanize and redeem the gruff, aggressive, violent male player character. Furthermore, the child sidekicks also serve to regulate the player’s in-game behaviour by way of a parasocial relationship. Using a close reading approach, I demonstrate that the supporting child-characters function as meta-critical devices to discipline gaming communities and the video game medium itself.